2009
DOI: 10.1186/1756-9966-28-97
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HER2 expression on cisplatin-based chemotherapy in advanced non-small cell lung cancer patients

Abstract: Introduction: The prognostic value of HER2 expression in patients with advanced non-small cell lung cancer remains controversial. The relationship between HER2 expression, and platinum resistance and patient survival, was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…35 However, in these studies, as well as in others, not all these features were confirmed to be associated with HER2 overexpression and in some instances were rejected. 27,30,31,[37][38][39][40] In addition to IHC assays, other authors have attempted to evaluate HER2 expression with other methodologies, such as real-time polymerase chain reaction assay. Brabender et al, 41 using a cutoff value of 1.8 ratio between lung tumors and normal tissues, reported that high HER2 mRNA levels were associated with an unfavorable prognosis and that the impact of HER2/EGFR co-expression on survival was additive (p = 0.176).…”
Section: Her2 Overexpression In Nsclcmentioning
confidence: 99%
“…35 However, in these studies, as well as in others, not all these features were confirmed to be associated with HER2 overexpression and in some instances were rejected. 27,30,31,[37][38][39][40] In addition to IHC assays, other authors have attempted to evaluate HER2 expression with other methodologies, such as real-time polymerase chain reaction assay. Brabender et al, 41 using a cutoff value of 1.8 ratio between lung tumors and normal tissues, reported that high HER2 mRNA levels were associated with an unfavorable prognosis and that the impact of HER2/EGFR co-expression on survival was additive (p = 0.176).…”
Section: Her2 Overexpression In Nsclcmentioning
confidence: 99%
“…Surprisingly, overexpression is associated with lower stage and grade of tumor [182]. Interestingly, there is an association of HER2/neu overexpression with NSCLC resistance to chemotherapy [183][184][185][186][187][188][189][190][191], which may account for the fact that HER2/neu overexpression is associated with a poor prognosis [35,[160][161][162][163][164][165][166][167][168][169][170][171][172][173] despite the association of HER2/neu overexpression with lower stage and grade. There is evidence for cooperativity and co-expression of HER1/EGFR [192], potentially associated with poorer prognosis [161,169,193], and there is data to support overexpression of HER2/neu as a mechanism for resistance to antibody inhibition of HER1/EGFR [194].…”
Section: Lungmentioning
confidence: 99%
“…The impact of expression could be analysed in process of determination of type of NSCLC treatment. It is known that in some cases, patients overexpressing HER2 are resistant to certain chemotherapeutic regimens, while the same patients have been proposed for therapy with monoclonal antibody-trastuzumab [23,24]. Due to small numto HER3 immunoreactivity of the tumors we found that: 11 (29.7 %) cancers were negative; 15 (40.5 %) shown low expression; 9 (24.3 %) had moderate expression and strong immunoreactivity in 2 (5.4 %) cases (Fig.…”
Section: Discussionmentioning
confidence: 99%